Pattern Replications (PATs) in the Speech of German-Polish Bilinguals - Jańczak, Barbara Alicja (2024)
This paper provides an insight into language induced changes in the speech of German-Polish bilinguals living in Germany and in Poland, with a focus on generational differences in the use of pattern replications (PATs). The relevance of the study of pattern replication in the speech of bilinguals is based on the fact that it has so far not attracted as much scientific interest as other linguistic phenomena resulting from frequent contact of two or more languages. Therefore, the article contributes to closing the research gap regarding the study of German-Polish language contact. The source of linguistic material for the analysis is language biographies of German-Polish bilinguals that have been recorded, by the author among others, transcribed, and annotated in regard to the morphosyntactic changes induced by German-Polish language contact. In particular, attention is paid to the interplay of bilingual language repertoires, focusing mainly on pattern replications (PATs). The peer group for the interview are two generations of Germans: Generation Poland and Generation Germany – the first are Germans who after World War 2, decided, or were forced to stay in the newly obtained Polish territories, the latter are descendants of the first group, living in Germany. The following presentation is based on the examples of pattern replications and statistical analysis of the linguistic changes resulting from language contact, developed on the basis of material published in the “LangGener” spoken corpus.
Keywords: German-Polish bilingualism; German minority in Poland; German-Polish language contact